Northern Helping Practitioners and the Phenomenon of Secondary Trauma - O'Neill, Linda K. (Canadian Journal of Counselling and Psychotherapy, 2010)
This article highlights a narrative inquiry study that considered the experience of and the effects on 8 northern helping practitioners (5 women, 3 men, ages 30–60) who have 7 to 40 years of experience in providing trauma support in isolated communities in north¬ern BC and the Yukon. Using a three-phase narrative analysis, 10 categories provided a structure for arranging the themes generated from the eight narratives. Six metathemes were interpreted from the data: helping takes over life, humanity, respectful engagement, invested and embedded, profoundly affected, and belief. Protective factors found in elements of embeddedness and connectiveness of practitioners and their motivation for doing the work they do emerged from the study.